2019
DOI: 10.1111/hsc.12832
|View full text |Cite
|
Sign up to set email alerts
|

Experiences of social work intervention among mothers with perinatal mental health needs

Abstract: Perinatal mental health difficulties are prevalent among women, and the vulnerability of young infants makes this a time when families experiencing multiple adversities may be particularly likely to attract state intervention. However, very little is known about how mothers experience social work intervention during the perinatal period. This study explored experiences of social work intervention among women with perinatal mental health difficulties. Qualitative semi‐structured interviews were carried out with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 23 publications
0
10
0
Order By: Relevance
“…Current specialist perinatal mental health service models often exclude certain groups (e.g., women with comorbid substance misuse problems and/or personality disorder or experiences of child removal by social services) 191 . There has been remarkably little research on how services can best help women with complex mental health needs that are likely to impact on the mother and the child.…”
Section: Service Deliverymentioning
confidence: 99%
“…Current specialist perinatal mental health service models often exclude certain groups (e.g., women with comorbid substance misuse problems and/or personality disorder or experiences of child removal by social services) 191 . There has been remarkably little research on how services can best help women with complex mental health needs that are likely to impact on the mother and the child.…”
Section: Service Deliverymentioning
confidence: 99%
“…A randomized control trial evaluating repeated nurse home visits demonstrated reduced levels of depression and stress in the intervention group ( Goldfeld et al, 2021 ). A similar study evaluating repeated home visits conducted by a social worker found that the intervention may result in elevated maternal stress levels ( Lever et al, 2019 ). A systematic review examining multi-modal group parenting programs found no significant improvement in maternal stress, anxiety or depression ( Waldrop et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Efforts to mitigate those negative effects include identifying and, when possible, addressing SDOH as part of clinical care, 5 which often means expanding the obstetric care team to include social workers and others. [6][7][8] Focusing on SDOH that raise legal issues, sometimes referred to as, "health-harming legal needs," 9 is a promising approach to expanding the types of SDOH that obstetric teams can help treat. By adding lawyers to the care team, medical-legal partnerships offer a pathway to help patients access direct legal services for specific SDOH.…”
Section: Using Medical-legal Partnerships To Fill Perinatal Care Gapsmentioning
confidence: 99%
“…Efforts to mitigate those negative effects include identifying and, when possible, addressing SDOH as part of clinical care, 5 which often means expanding the obstetric care team to include social workers and others. 6 8 …”
Section: Using Medical–legal Partnerships To Fill Perinatal Care Gapsmentioning
confidence: 99%